Differentiation of Mouse Induced Pluripotent Stem Cells Into Alveolar Epithelial Cells In Vitro for Use In Vivo. (24th April 2014) - Zhou, Qiliang; Ye, Xulu; Sun, Ruowen; Matsumoto, Yoshifumi; Moriyama, Masato; Asano, Yoshiya; Ajioka, Yoichi; Saijo, Yasuo
Abstract : This study reports a simple and rapid protocol for in vitro differentiation of mouse induced pluripotent stem cells (iPSCs) into alveolar epithelial cells. Differentiated iPSCs show potential for regenerating three-dimensional alveolar lung structure and can be used to abrogate lung injury. Abstract: : Alveolar epithelial cells (AECs) differentiated from induced pluripotent stem cells (iPSCs) represent new opportunities in lung tissue engineering and cell therapy. In this study, we modified a two-step protocol for embryonic stem cells that resulted in a yield of ∼9% surfactant protein C (SPC) + alveolar epithelial type II (AEC II) cells from mouse iPSCs in a 12-day period. The differentiated iPSCs showed morphological characteristics similar to those of AEC II cells. When differentiated iPSCs were seeded and cultured in a decellularized mouse lung scaffold, the cells reformed an alveolar structure and expressed SPC or T1α protein (markers of AEC II or AEC I cells, respectively). Finally, the differentiated iPSCs were instilled intratracheally into a bleomycin-induced mouse acute lung injury model. The transplanted cells integrated into the lung alveolar structure and expressed SPC and T1α. Significantly reduced lung inflammation and decreased collagen deposition were observed following differentiated iPSC transplantation. In conclusion, we report a simple and rapid protocol for in vitro differentiation of mouse iPSCs into AECs. Differentiated iPSCs show potential for regenerating three-dimensional alveolar lung structure and can be used to abrogate lung injury.